Academic Services in Learning Commons of Academic Libraries: An Answer to the Current Educational Requirements - González-Martínez, Larisa (2021)
Undoubtedly, the library is a service-oriented institution, which has a deep social dimension. This means, among many things, a relationship between society and the library. Because of this, the social group influences the configuration of the information center that affects each of its processes, including its services. The university libraries involved in this kind of dynamics, which is why they have due to educational requirements, making room to Learning Commons (LC) have generated changes in the services they offer to their users. Given this situation, this article proposes the concept of academic services to support the universities, through transversality, gradualness, flexibility, innovation, dynamism, teamwork, co-responsibility and the skills of the librarian.